2009
DOI: 10.1021/la900166u
|View full text |Cite
|
Sign up to set email alerts
|

Cell Attachment Behavior on Solid and Fluid Substrates Exhibiting Spatial Patterns of Physical Properties

Abstract: The ability to direct proliferation and growth of living cells using chemically and topologically textured surfaces is finding many niche applications, both in fundamental biophysical investigations of cell-surface attachment as well as in developing design principles for many tissue engineering applications. Here we address cellular adhesion behavior on solid patterns of differing wettability (a static substrate) and fluid patterns of membrane topology (a dynamic substrate). We find striking differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Thus, island A2P, which takes into account island shape and dimensions, may be important criterion for other cell behaviors and for accurate seeding 3,25,29,30 . This simulation could help to determine if the morphological switch observed here is enabled or prohibited by island geometry for more specific and complex geometries, such as on crosses or grids, 25,31‐33 annular rings, 7,25,34 or sinusoidal bands 7 …”
Section: Discussionmentioning
confidence: 90%
“…Thus, island A2P, which takes into account island shape and dimensions, may be important criterion for other cell behaviors and for accurate seeding 3,25,29,30 . This simulation could help to determine if the morphological switch observed here is enabled or prohibited by island geometry for more specific and complex geometries, such as on crosses or grids, 25,31‐33 annular rings, 7,25,34 or sinusoidal bands 7 …”
Section: Discussionmentioning
confidence: 90%
“…In addition, intricate SLBs were developed with gradients of ligands for cells and with stimuli‐responsive ligands to modulate cell adhesion. [8a,11] Despite these intriguing achievements, there are however only few examples where cell–SLB interactions have been targeted beyond initial cell adhesion events. [9a,10c,g,g–i] For example, Evans et al anchored N ‐cadherin ectodomains to SLBs to study the behavior of periosteum derived progenitor cells on these SLBs .…”
Section: Introductionmentioning
confidence: 99%
“…The combination with microchannels is especially promising since this concept provides the opportunity to integrate on chip detection schemes to perform (single) cell stimulation studies or for the creation of heterogenous arrays76 using nanodisks 77. Alternative photolithography‐based approaches involve the formation of a photoresist prepattern and their transfer into a substrate containing SLB adhesive areas embedded in a non‐interacting background or a contrast of lipid bilayers and lipid monolayers 78. For instance, Rossetti et al15 c] showed that an area‐selective SLB patterning via liposome fusion was achievable on a TiO 2 /SiO 2 metal oxide prepatterned substrate.…”
Section: Supported Lipid Bilayer Arrays For Biosensing Applicationsmentioning
confidence: 99%